Detection of virulence determinants and its association with drug resistance in clinical isolates of Pseudomonas aeruginosa - S., Pramodhini; S., Umadevi; K. S., Seetha (International Journal of Research in Medical Sciences, 2016)
Background: Pseudomonas aeruginosa is most commonly noted significant nosocomial pathogen, because of its distribution, of multi drug resistance and expression of various virulence factors. This study was aimed to detect various resistance mechanism and virulence factors of Pseudomonas aeruginosa and to determine the significant association between them. Methods: A total of 203 clinical isolates of Pseudomonas aeruginosa were included in this study. All isolates were detected for various virulence factors like Phospholipase, Hemolysin, Gelatinase and DNAse. Screening of β-lactamase like extended spectrum beta-lactamase (ESBL), AmpC beta-lactamase and Metallo β-lactamase (MBL) of Pseudomonas aeruginosa were also done. Results: Of total 203 isolates of Pseudomonas aeruginosa studied, 103 were from pus, 50 each from urine and respiratory samples. Virulence factors distribution of Pseudomonas aeruginosa showed 80.3% ,70% , 71.4% , 44.8% and 34% were positive for hemolysin, phospholipase, gelatinase, DNAse and biofilm production respectively. Study on prevalence of various β-lactamase in Pseudomonas aeruginosa isolated showed 25.6%, 24.1% and 10.3% were ESBL, MBL and AmpC producers respectively. Conclusions: This study suggests that production of virulence factors may not be significantly associated with antibiotic resistance. However, expression of certain virulence factors, most notably hemolysin and DNAse activity were significantly associated with β-lactamase production. Hence forth, future trends in clinical microbiology laboratories should focus on development of tests for the rapid detection of the most important virulence markers in addition to identification of pathogens and susceptibility pattern.